Enhancing senior high school students' systems thinking through the biology grand arena: Evidence from a life-system-based biology competition - Ririn Mardiana Saputri; Maria Gaudensia Ladja; Novantrya Salidar; S. Suwarinah; Bambang Supriatno; Sariwulan Diana; S. Saefudin (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Systems thinking is an essential competency for understanding the complexity of biological systems, yet many secondary school students continue to experience difficulties in integrating biological concepts across organizational levels. Objectives: This study investigated the effectiveness of the Biology Grand Arena, a life-system-based biology competition, in enhancing senior high school students’ systems thinking skills. Methods: A one-group pretest–posttest pre-experimental design was employed involving 188 students from 14 senior high schools in East Java, Indonesia. Students participated in five competition arenas that integrated biological phenomena across molecular, organismal, and ecological levels. Systems thinking was assessed using a validated essay-based instrument aligned with the hierarchical framework of systems thinking. Data were analyzed using the Wilcoxon signed-rank test and normalized gain (N-gain) analysis. Results: The findings revealed a significant improvement in students’ systems thinking after participation in the Biology Grand Arena, with moderate overall learning gains. Improvement varied across competition arenas, indicating that different biological contexts provided different opportunities for developing systems thinking. Conclusion: These findings suggest that life-system-based competition can serve as an innovative complementary learning approach to foster higher-order biological reasoning beyond conventional classroom instruction. The study contributes empirical evidence supporting competition-based learning as a promising strategy for promoting systems thinking in secondary biology education.